ChemInform Abstract: Copper‐Catalyzed Vicinal Oxyazidation and Diazidation of Styrenes under Mild Conditions: Access to Alkyl Azides. Issue 17 (April 2016) - Lu, Ming‐Zhu; Wang, Cheng‐Qiang; Loh, Teck‐Peng
Abstract: A novel vicinal oxyazidation and diazidation of styrenes (I) using the stable azidoiodine reagent (II) as an azide source is described.